2010
DOI: 10.1136/qshc.2007.024992
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a tele-ICU on provider attitudes about teamwork and safety climate

Abstract: Objective To measure teamwork and safety climate in three intensive care units (ICUs) before and after remote monitoring by intensivists using telemedicine technology (tele-ICU). Design Controlled pre tele-ICU and post tele-ICU crosssectional survey. Setting ICUs in two non-teaching community hospitals and one tertiary care teaching hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Our result is similar to the findings of Chu-Weininger et al [11], in which nurses in a tele-ICU showed improvement in perceptions of safety and teamwork climate. In addition, our study showed that the perception of care in the control unit actually worsened during the time of study.…”
Section: E13supporting
confidence: 94%
See 2 more Smart Citations
“…Our result is similar to the findings of Chu-Weininger et al [11], in which nurses in a tele-ICU showed improvement in perceptions of safety and teamwork climate. In addition, our study showed that the perception of care in the control unit actually worsened during the time of study.…”
Section: E13supporting
confidence: 94%
“…Most of the tele-ICU services are provided and used by nurses in the telemedicine center and at the bedside, respectively [10] . Although improving patient care through telemedicine can potentially improve the satisfaction of bedside staff with the overall care environment, only 1 study has addressed perceptions of tele-ICU [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…environment. Although the moderate job satisfaction domain was not positive in the other studies [11,14,[22][23][24], ICU nurses stoutly agreed that they "like their job" (98.4%) and valued their hospital as a "good place to work" (95.9%); these 2 variables suggest that there is a high working morale among ICU nurses despite parallel complaints for fatigue and exhaustion. Although there was comparable less agreement that moral in this ICU area is high, positive scores are very high, indicating a strong commitment of the ICU nurses to their job.…”
Section: Discussionmentioning
confidence: 89%
“…• Transitions and Handoffs [50,51] • Evaluation of Health IT [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] • Foundations of Health IT [68][69][70][71][72][73][74][75][76][77][78][79][80][81] • Commentaries [82][83][84][85][86] …”
Section: Citation Analysismentioning
confidence: 99%